A combat casualty relevant dismounted complex blast injury model in swine. (12th August 2022) - Cralley, Alexis L.; Moore, Ernest E.; Kissau, Daniel; Coleman, Julia R.; Vigneshwar, Navin; DeBot, Margot; Schaid, Terry R.; Moore, Hunter B.; Cohen, Mitchell J.; Hansen, Kirk; Silliman, Christopher C.; Sauaia, Angela; et al.
Abstract : A novel Dismounted Complex Blast Injury translation animal model; Tactical Combat Casualty Care Guidelines for DCBI Abstract : BACKGROUND: Improvised explosive devices have resulted in a unique polytrauma injury pattern termed dismounted complex blast injury (DCBI), which is frequent in the modern military theater. Dismounted complex blast injury is characterized by extremity amputations, junctional vascular injury, and blast traumatic brain injury (bTBI). We developed a combat casualty relevant DCBI swine model, which combines hemorrhagic shock (HS) and tissue injury (TI) with a bTBI, to study interventions in this unique and devastating military injury pattern. METHODS: A 50-kg male Yorkshire swine were randomized to the DCBI or SHAM group (instrumentation only). Those in the DCBI group were subjected to HS, TI, and bTBI. The blast injury was applied using a 55-psi shock tube wave. Tissue injury was created with bilateral open femur fractures. Hemorrhagic shock was induced by bleeding from femoral arteries to target pressure. A resuscitation protocol modified from the Tactical Combat Casualty Care guidelines simulated battlefield resuscitation for 240 minutes. RESULTS: Eight swine underwent the DCBI model and five were allocated to the SHAM group. In the DCBI model the mean base excess achieved at the end of the HS shock was −8.57 ± 5.13 mmol·L −1 . A significant coagulopathy was detected in the DCBI model as measured by prothrombin time (15.8 seconds DCBI vs. 12.86 seconds SHAM; p = 0.02) and thromboelastography maximum amplitude (68.5 mm DCBI vs. 78.3 mm in SHAM; p = 0.0003). For the DCBI models, intracranial pressure (ICP) increased by a mean of 13 mm Hg, reaching a final ICP of 24 ± 7.7 mm Hg. CONCLUSION: We created a reproducible large animal model to study the combined effects of severe HS, TI, and bTBI on coagulation and ICP in the setting of DCBI, with significant translational applications for the care of military warfighters. Within the 4-hour observational period, the swine developed a consistent coagulopathy with a concurrent brain injury evidenced by increasing ICP. Abstract :